Proprietary Knowledge Protection and Product Market Performance - Nguyen, Justin Hung; Pham, Peter; Qiu, Buhui (Journal of Financial and Quantitative Analysis, 2023)
Abstract Does proprietary knowledge protection (PKP) spur or hinder the product-market performance of new firms? Exploiting the staggered adoptions of the inevitable disclosure doctrine by U.S. State Courts, which enhance PKP, we show that treated firms increase industry-adjusted sales growth by 2% compared to control firms. The effect is concentrated among small and young firms and increases with the scope of proprietary knowledge and rivals’ access to external finance. PKP encourages firms to develop new products and stimulates initial public offering activity. Our results suggest that PKP alleviates predation risk associated with “deep-pocket” rivals by allowing firms to maintain competitive advantages.